(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
In this article, examples of similarity between the concept of "man” and woman in the karakalpak language and the differences in its usage in the lexical context of written and spoken and the differences in its usage in other Turkic languages have been presented through analysis.